Skeletal muscle fibers produce B-cell stimulatory factors in chronic myositis - Carstens, Per-Ole; Müllar, Luisa M.; Wrede, Arne; Zechel, Sabrina; Wachowski, Martin M.; Brandis, Almuth; Krause, Sabine; Zierz, Stephan; Schmidt, Jens (Frontiers in Immunology, 2023)
Introduction: To identify B-cell-mediated immunomechanisms in Inclusion body myositis (IBM) and polymyositis (PM) as part of the complex pathophysiology. Materials and Methods: Human primary myotube cultures were derived from orthopedic surgery. Diagnostic biopsy specimen from patients with IBM (n=9) and PM (n=9) were analyzed for markers of B cell activation (BAFF, APRIL) and for chemokines that control recruitment of B cells (CXCL-12, CXCL-13). Results were compared to biopsy specimen without myopathic changes (n=9) and hereditary muscular dystrophy (n=9). Results: The mRNA-expression of BAFF, APRIL and CXCL-13 was significantly higher in IBM and PM compared to controls. Patients with IBM displayed the highest number of double positive muscle fibers for BAFF and CXCL-12 (48%) compared to PM (25%), muscular dystrophy (3%), and non-myopathic controls (0%). In vitro exposure of human myotubes to pro-inflammatory cytokines led to a significant upregulation of BAFF and CXCL-12, but APRIL and CXCL-13 remained unchanged. Conclusions: The results substantiate the hypothesis of an involvement of B cell-associated mechanisms in the pathophysiology of IBM and PM. Muscle fibers themselves seem to contribute to the recruitment of B cells and sustaining the inflammation.